2020
DOI: 10.1038/s41467-020-18947-y
|View full text |Cite
|
Sign up to set email alerts
|

AKAP5 complex facilitates purinergic modulation of vascular L-type Ca2+ channel CaV1.2

Abstract: The L-type Ca2+ channel CaV1.2 is essential for arterial myocyte excitability, gene expression and contraction. Elevations in extracellular glucose (hyperglycemia) potentiate vascular L-type Ca2+ channel via PKA, but the underlying mechanisms are unclear. Here, we find that cAMP synthesis in response to elevated glucose and the selective P2Y11 agonist NF546 is blocked by disruption of A-kinase anchoring protein 5 (AKAP5) function in arterial myocytes. Glucose and NF546-induced potentiation of L-type Ca2+ chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 68 publications
2
35
0
1
Order By: Relevance
“…However, our published (7) data showed that there is little difference in the gating properties of K ATP channels between vehicle-treated and leptin-treated cells, suggesting that the effect of altered PKA and/or PP2B signaling following leptin stimulation affects primarily K ATP channel trafficking rather than gating. Also important, while our current study focuses on the role of AKAP79/150 in mediating PKA signaling by leptin, AKAP79/150 is multifaceted and can coordinate multiple signaling complexes, as has been shown in neurons (39,42,72) and other cell types (66,73). Thus, AKAP79/150 in β-cells may be involved in organizing multiple signaling networks with distinct functions.…”
Section: Implications For the Role Of Akap79/150 In Insulin Secretionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, our published (7) data showed that there is little difference in the gating properties of K ATP channels between vehicle-treated and leptin-treated cells, suggesting that the effect of altered PKA and/or PP2B signaling following leptin stimulation affects primarily K ATP channel trafficking rather than gating. Also important, while our current study focuses on the role of AKAP79/150 in mediating PKA signaling by leptin, AKAP79/150 is multifaceted and can coordinate multiple signaling complexes, as has been shown in neurons (39,42,72) and other cell types (66,73). Thus, AKAP79/150 in β-cells may be involved in organizing multiple signaling networks with distinct functions.…”
Section: Implications For the Role Of Akap79/150 In Insulin Secretionmentioning
confidence: 85%
“…smooth muscle cells also illustrates how local cAMP-PKA signaling in an AKAP79/150-organized complex can dictate a very different downstream cellular response from that regulated by more global engagement of cAMP and PKA (66). Of note, some AKAPs expressed in β-cells, including AKAP79/ 150, have already been implicated in either inhibiting or promoting insulin secretion (20)(21)(22)(23)(24)(25).…”
Section: Spatiotemporal Regulation Of Pka Activity In β-Cellsmentioning
confidence: 98%
“…This raises the possibility that the reduced GSIS observed in AKAP150ΔPIX-expressing islets is in part due to increased K ATP channel surface expression. Also important, while our current study focuses on the role of AKAP79/150 in mediating PKA activation by leptin, AKAP79/150 is multifaceted and can coordinate multiple signaling complexes, as has been shown in neurons 39,42,67 and other cell types 66,68 . Thus, AKAP79/150 in β-cells may be involved in organizing multiple signaling networks with distinct functions.…”
Section: Discussionmentioning
confidence: 98%
“…229 In response to several stimuli, in particular an increase in glucose in patients with diabetes, PKA phosphorylates Cav1.2 at Ser1928, which increases their open probability and thereby the intracellular Ca 2+ promoting excessive vasoconstriction. 230,231 Nanodomains identified in vessels can also be involved in the regulation of blood pressure in kidney arteries. The interaction between Kv7.4, G βγ -subunits and AKAPanchored PKA is responsible for kidney artery relaxation.…”
Section: Control Of Blood Pressure By Camp From Outside the Kidneymentioning
confidence: 99%
“…In the sarcolemma of arterial VSMCs and in the vicinity of AC5, AKAP150 anchors PKA, PKC, and CaN and binds the pore‐forming subunit (αC1) of the Cav1.2 L‐type Ca 2+ channel 229 . In response to several stimuli, in particular an increase in glucose in patients with diabetes, PKA phosphorylates Cav1.2 at Ser1928, which increases their open probability and thereby the intracellular Ca 2+ promoting excessive vasoconstriction 230,231 …”
Section: A Role Of Camp For the Ckd Risk Factors Hypertension And Dmmentioning
confidence: 99%